EFEKTIVITAS PENGGUNAAN MEDIA MANIPULATIF DALAM PEMBELAJARAN OPERASI BILANGAN BULAT DI SMP SWADAYA KESAMBEN - Djenar Mahesa Ayu Sadela; Eny Suryowati (LPPM Institut Ahmad Dahlan Probolinggo, 2026)
This study aims to know the effectiveness of manipulative media in improving the understanding of integer operations among seventh-grade junior high school students. The research method employed a one-group pretest-posttest design. The population of this study consisted of seventh-grade students at SMP Swadaya Kesamben, with the sample being students from class VII A. The research instrument was a validated test on integer operations. The results showed a difference in students’ average learning outcomes before and after the use of button-based manipulative learning media. This finding aligns with Bruner’s theory of concrete learning and previous studies on the benefits of manipulative media. Therefore, it can be concluded that manipulative media are effective in enhancing seventh-grade students’ understanding of integer operations. The pedagogical implication suggests that teachers should implement manipulative media in mathematics instruction. Further research may explore the development of digital manipulative media for more interactive learning experiences.